Perceptions of gender roles and freedom among Iranian international students in Hungary. (January 2022) - Hosseini-Nezhad, Sara; Safdar, Saba; Nguyen Luu, Lan Anh
Abstract: This qualitative study investigated attitudes toward gender roles and perception of freedom among Iranian students ( n  = 20) in Hungary. Four topics were extracted from the abductive content analysis of semi-structured interview transcripts: (1) gender essentialism, (2) gender-role egalitarianism, (3) traditional gender stereotypes, and (4) gendered freedom. Results indicated that: many men adopted gender essentialism, although women did not; men held transitional gender-role attitudes, whereas women held egalitarian gender-role attitudes; men generally displayed greater gender stereotypes and sexism as compared to women; almost all students, regardless of gender, endorsed gender equality and freedom and reported feeling more freedom in Hungary than in Iran; although, women expressed greater outrage over gender inequality and put greater emphasis on gender role differences; some forms of freedom in Hungary seemed to be more of a privilege to one gender than the other (e.g., no veiling requirement for women and relaxed cross-gender relationship for men).